Cholinergic inhibition of short (outer) hair cells of the chick's cochlea - Fuchs, PA (J Neurosci, 1992)
Cochlear hair cells are thought to be inhibited by the release of ACh from efferent neurons. Several studies have implicated Ca2+ as a postsynaptic intermediary in hair cell inhibition, but its role remains unproven. We have made whole-cell, tight-seal recordings from single short hair cells (the avian analog of outer hair cells in the mammalian cochlea), isolated from the chick's cochlea, to determine the mechanism of cholinergic inhibition. These cells hyperpolarized upon exposure to ACh, although a brief depolarization preceded the much larger, longer- lasting hyperpolarization. In voltage clamp ACh evoked an outward current that reversed in sign near the K+ equilibrium potential. A small, transient inward current preceded the predominant outward current. The ACh-evoked K+ current depended on Ca2+ in the external saline, or could be prevented when the cell was dialyzed with the rapid Ca2+ buffer BAPTA. In BAPTA-loaded cells a residual inward current was seen. This activated with very little delay upon exposure of the cell to ACh and reversed near 0 mV membrane potential. Thus, the hair cell ACh receptor appears to be a nonspecific cation channel through which Ca2+ enters and triggers the opening of nearby Ca(2+)-activated K+ channels. However, the ACh-evoked K+ channels are not the same as the “maxi” K+ channels activated by Ca2+ influx through voltage-gated Ca2+ channels in these same cells.